DEVELOPING LANGUAGE SKILLS USING AUTHENTIC MATERIALS - Petrosyan.N.V; Misirov Asadbek Amirqul o‘g‘li; Ne‘matov Lazizbek Qo‘chqorboy o‘g‘li (TADQIQOTLAR, 2026)
Abstract.  This  article  scientifically  analyzes  the  role,  importance  and effectiveness of using authentic materials in the language teaching process. Authentic texts,  audio  and  video  resources  are  considered  as  important  tools  in  developing students'  listening  comprehension,  reading,  writing  and  speaking  skills.  The  article covers the types of authentic materials, methods of integrating them into the teaching process,  their  advantages  and  problems  encountered.  It  also  provides  practical recommendations  on  creating  real  communicative  situations  in  language  teaching, increasing  cultural  competence  and  increasing  students'  motivation.  Keywords: authentic  materials,  language  skills,  communicative  approach,  listening comprehension, reading skills, writing skills, speaking skills, authentic texts, cultural competence, methodology, innovative approach.